Leptin-mediated increases in catecholamine signaling reduce adipose tissue inflammation via activation of macrophage HDAC4 - Luan, Bing; Goodarzi, Mark O; Phillips, Naomi G; Guo, Xiuqing; Chen, Yii-Der I; Yao, Jie; Allison, Matthew; Rotter, Jerome I; Shaw, Reuben; Montminy, Marc (Cell metabolism, 2014)
Obesity promotes systemic insulin resistance through inflammatory changes that lead to the release of cytokines from activated macrophages. Although the mechanism is unclear, the second messenger cAMP has been found to attenuate macrophage activity in response to a variety of hormonal signals. We show that, in the setting of acute overnutrition, leptin triggers catecholamine-dependent increases in cAMP signaling that reduce inflammatory gene expression via the activation of the histone deacetylase HDAC4. cAMP stimulates HDAC4 activity through the PKA-dependent inhibition of the salt-inducible kinases (SIKs), which otherwise phosphorylate and sequester HDAC4 in the cytoplasm. Following its dephosphorylation, HDAC4 shuttles to the nucleus where it inhibits NF-κB activity over proinflammatory genes. As variants in the Hdac4 gene are associated with obesity in humans, our results indicate that the cAMP-HDAC4 pathway functions importantly in maintaining insulin sensitivity and energy balance via its effects on the innate immune system.